Macroeconomic-Specific Determinants of Insurers Solvency in Developing Economies - Aluko, Timothy Olaniyi; Makumbe, Kudakwashe Carol (Acta Universitatis Danubius. Œconomica, 2025)
The paper examines the macroeconomic factors and requirements that influence insurance solvency in Zimbabwe. It aims to develop a conceptual framework for policymakers to analyse economic conditions and establish an effective risk-based capital system. This framework intends to motivate insurers to reduce insolvency risks, support the rehabilitation of weaker insurers, and facilitate the orderly exit of unsuccessful firms from the market. Using content analysis and a framework approach, the study identifies patterns and contexts related to insurers’ solvency in Zimbabwe. The study utilised data from secondary sources, including reports from seventeen non-life insurance companies covering the period from 2017 to 2022, sourced from the Insurance and Pensions Commission in Zimbabwe. The analysis reveals that liquidity risks, liquid assets, capital, balance sheets, shareholders’ funds, gross domestic product, interest rates, inflation, and governance all play essential roles in determining insurer solvency in developing nations, such as Zimbabwe. However, a poorly designed system may encourage excessive risk-taking by insurers, impose unnecessary costs on policyholders and financially stable insurers, and reduce overall market capacity. To prevent these issues, any proposed risk-based capital system should be thoroughly tested before implementation to ensure it functions effectively, particularly in areas with a high proportion of past insolvencies. Therefore, a robust regulatory framework for insurance companies in developing nations will help manage solvency levels, aiming to reduce the insolvency of short-term insurers and generate sufficient revenue to cover their expenses.